Biological control of strawberry crown rot, root rot and grey mould by the beneficial fungus Aureobasidium pullulans - Mudassir Iqbal; Maha Jamshaid; Muhammad Awais Zahid; Erik Andreasson; Ramesh R. Vetukuri; Johan A. Stenberg (BioControl, 2021)
Utilization of biocontrol agents is a sustainable approach to reduce plant diseases caused by fungal pathogens. In the present study, we tested the effect of the candidate biocontrol fungus Aureobasidium pullulans (De Bary) G. Armaud on strawberry under in vitro and in vivo conditions to control crown rot, root rot and grey mould caused by Phytophthora cactorum (Lebert and Cohn) and Botrytis cinerea Pers, respectively. A dual plate confrontation assay showed that mycelial growth of P. cactorum and B. cinerea was reduced by 33–48% when challenged by A. pullulans as compared with control treatments. Likewise, detached leaf and fruit assays showed that A. pullulans significantly reduced necrotic lesion size on leaves and disease severity on fruits caused by P. cactorum and B. cinerea . In addition, greenhouse experiments with whole plants revealed enhanced biocontrol efficacy against root rot and grey mould when treated with A. pullulans either in combination with the pathogen or pre-treated with A. pullulans followed by inoculation of the pathogens. Our results demonstrate that A. pullulans is an effective biocontrol agent to control strawberry diseases caused by fungal pathogens and can be an effective alternative to chemical-based fungicides.